Clifford's Happy Easter - Bridwell, Norman (New York : Scholastic, 1994)
After dying Easter eggs, Clifford's owner has a very colorful dream.
In logo on cover: Clifford, the big red dog.
K-3
Keywords: Easter -- Fiction; Easter eggs -- Fiction; Dreams -- Fiction; Dogs -- Fiction; Dogs -- Fiction; Easter stories